165k views
22 votes
10. Selena says that (a - b)2 and (b-a)2 are equivalent expressions. Do you

agree or disagree? Justify your answer with work or a valid explanation.

1 Answer

4 votes

Answer:

I agree.

Explanation:

(a - b)² compared to (b - a)²

Work with (b - a)².

(b - a)² =

Factor -1 out of b - a.

= [-1(-b + a)]²

Apply the exponent to the two factors of the multiplication.

= (-1)²(a - b)²

= 1(a - b)²

= (a - b)²

We just proved that (a - b)² = (b - a)².

Selena is correct.

User Wouter Van Ooijen
by
4.7k points